The effect of Pr substitution at sr sites in 110K phase of (Bi-Pb)-Sr-Ca-Cu-O superconducting ceramics / Nazarin Nordin - Nordin, Nazarin (2007)
The effect of magnetic Praseodymium (Pr) substitutional doping at varying concentration into the Strontium (Sr) site in the Bi-Sr-Ca-Cu-0 (BSCCO) high temperature superconductor is investigated. The samples are prepared via solid state reaction method and underwent sintering, annealing and resintering process. The two measured properties are the electrical and the structural properties according to the stoichiometric formula (Bii6Pbo.4)-(Sri.JtPrt)2-Ca2-Cu3-05 where x = 0.0 - 0.5. For all series of doping concentration, x = 0.0 - 0.5, Tc (onset) decreased for x = 0.1, then slightly increased at x = 0.2. The Tc then gradually decreased as x is increased and approaches zero as x > 0.5. The onset of critical temperature Tc and zero resistance critical temperature Tc (R=O) as x increases indicated the superconductivity destructive trend. Interestingly, at x = 0.2, the destructive trend was reversed, but as x > 0.2, critical transition temperature is lowered. Critical current density, jc was also optimised for x = 0.2 samples. Longer sintering and annealing also improves the Tc and this is shown in x - 0.2 sample. At x = 0.2 sample, the Tc (onset) for sintered, annealed (at 820 °C) and resintered samples are nearly identical to pure sample.